Production of d-xylonic acid using a non-recombinant Corynebacterium glutamicum strain. (November 2018) - Tenhaef, Niklas; Brüsseler, Christian; Radek, Andreas; Hilmes, René; Unrean, Pornkamol; Marienhagen, Jan; Noack, Stephan
Highlights: C. glutamicum Δ iolR efficiently converts d -xylose to d -xylonate. The putative myo -inositol 2-dehydrogenase IolG can catalyze oxidation of d -xylose. Fed-batch operation enables maximum product yield and high volumetric productivity. Development of a cost-efficient feedstock based on hydrolyzed sugarcane bagasse. One-pot sequential hydrolysis and fermentation process for d -xylonate production. Abstract: It was found that Corynebacterium glutamicum Δ iolR devoid of the transcriptional regulator IolR accumulates high amounts of d -xylonate when cultivated in the presence of d -xylose. Detailed analyses of constructed deletion mutants revealed that the putative myo -inositol 2-dehydrogenase IolG also acts as d -xylose dehydrogenase and is mainly responsible for d -xylonate oxidation in this organism. Process development for d -xylonate production was initiated by cultivating C. glutamicum Δ iolR on defined d -xylose/d -glucose mixtures under batch and fed-batch conditions. The resulting yield matched the theoretical maximum of 1 mol mol −1 and high volumetric productivities of up to 4 g L −1 h −1 could be achieved. Subsequently, a novel one-pot sequential hydrolysis and fermentation process based on optimized medium containing hydrolyzed sugarcane bagasse was developed. Cost-efficiency and abundance of second-generation substrates, good performance indicators, and enhanced market access using a non-recombinant strain open the perspective for a commercially viable bioprocess for d -xylonate production in the near future.